A Characterization of Ophthalmology Residency Program Social Media Presence and Activity - Hasenin Al-khersan; Rebecca Tanenbaum; Thomas A. Lazzarini; Nimesh A. Patel; Jayanth Sridhar (Journal of Academic Ophthalmology, 2020)
Objective To determine the presence and activity of ophthalmology departments associated with residency programs on social media platforms and the use of these social media platforms by residency applicants. Design Cross-sectional online assessment of ophthalmology training program departments' presence and activity on Facebook, Twitter, and Instagram. Participants A total of 120 accredited ophthalmology residency training programs and 498 ophthalmology residency applicants. Methods Each department was evaluated by (1) searching for social media links on the department's Web site, (2) searching for the department on Facebook, Twitter, and Instagram, and (3) searching on Google. A simultaneous survey was conducted to assess social media platform use of 2019 to 2020 ophthalmology residency application cycle candidates. Main Outcomes The presence of ophthalmology departments on Facebook, Twitter, and Instagram, as well as the total number of followers and posts during January 2020. Results Of 120 programs evaluated, 45 programs (37.5%) had a Facebook page, 29 (24.3%) were on Twitter, and 22 (18.3%) had an Instagram page. Among top 20 Doximity-ranked ophthalmology programs, 80% had at least one social media page on Facebook, Twitter, or Instagram compared with 33% among the remainder of programs (chi-square test = 15.2, p < 0.001). Top 20 programs also had more followers compared with others on Facebook (4,363 vs. 696, respectively, p < 0.0001) and Twitter (3,673 vs. 355, respectively, p = 0.007) but not on Instagram (1,156 vs. 1,687, respectively, p = 0.71). Among 498 residency applicants to Bascom Palmer Eye Institute from the 2019 to 2020 cycle, 159 (31.9%) responded to a survey regarding their use of social media during the application process. In total, 54 (34%) responded that they used social media to evaluate residency programs. Conclusion Departments of top 20 ophthalmology residency had both a greater presence and following on social media compared with other departments. While Facebook was the most used platform by ophthalmology departments, applicants most commonly used Instagram. As applicants come to use these social media resources more frequently, ophthalmology residency programs may increasingly benefit from maintaining an active social media page.